1983
DOI: 10.1126/science.6879184
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Synthesis in the Brain and Increased Turnover in Hypertensive Rats

Abstract: The missing link in the evidence for an active endogenous renin angiotensin system in the brain has been the demonstration of local angiotensin synthesis in the central nervous system in vivo. In this report the extraction and characterization of angiotensin I and angiotensin II from the brain of rats is described. The accumulation of angiotensin I was enhanced in hypertensive rats when the conversion to angiotensin II was blocked in vivo by the converting enzyme inhibitor captopril.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
117
3
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(128 citation statements)
references
References 15 publications
6
117
3
2
Order By: Relevance
“…In this regard, estimates of cross-reactivity using either RIA ( 5 ) or immunoblots (35) indicate that the ANG I1 antisera cross-react primarily with ANG I1 and, to a lesser extent, with angiotensin I and angiotensin 111. The latter is only present in low concentrations in the mammalian brain (4). In the present study, immunoreactivity to ANG I1 could be completely abolished by preabsorption of a working dilution of the antibody with 15 pg of purified Ile5-ANG 11.…”
Section: Circurnvrntriculur Organs-sites Without a Blood-bruin Burriersupporting
confidence: 50%
See 1 more Smart Citation
“…In this regard, estimates of cross-reactivity using either RIA ( 5 ) or immunoblots (35) indicate that the ANG I1 antisera cross-react primarily with ANG I1 and, to a lesser extent, with angiotensin I and angiotensin 111. The latter is only present in low concentrations in the mammalian brain (4). In the present study, immunoreactivity to ANG I1 could be completely abolished by preabsorption of a working dilution of the antibody with 15 pg of purified Ile5-ANG 11.…”
Section: Circurnvrntriculur Organs-sites Without a Blood-bruin Burriersupporting
confidence: 50%
“…Ganten et al (4) isolated angiotensin I and A N G II from the rat brain and demonstrated the central nature of ANG I1 production by the intracerebroventricular administration of an inhibitor of angiotensin-converting enzyme which caused a reduction in local ANG 11. Furthermore, the presence of each of the components of the renin angiotensin system (RAS) has been demonstrated immunocytochemically (5)(6)(7)(8) and the likelihood of local production supported by the identification of mRNA for renin and angiotensinogen (9,10).…”
mentioning
confidence: 99%
“…Young SHR have been reported to have elevated turnover and levels of Ang II in the brain. 4,45 SHR have also been reported to be hyperresponsive to the effects of intracerebroventricular Ang II and Ang III. 46 In membrane preparations from SHR and WKY brains, Ang II is metabolized more rapidly by SHR than by WKY but Ang III metabolism is similar.…”
mentioning
confidence: 99%
“…The research in Detlev Ganten's laboratory was stimulating. The role for a renin-aniotensin system in the brain conducting cardiovascular regulation, salt-and-water appetite, and even controlling energy metabolism is now well established [3,4]. Natriuretic peptides had been discovered, but developing an assay to measure natriuretic peptides brought this line of research into the clinical arena [5].…”
mentioning
confidence: 99%